2018
DOI: 10.1101/gr.234104.117
|View full text |Cite
|
Sign up to set email alerts
|

Defining TP53 pioneering capabilities with competitive nucleosome binding assays

Abstract: Accurate gene expression requires the targeting of transcription factors (TFs) to regulatory sequences often occluded within nucleosomes. The ability to target a TF binding site (TFBS) within a nucleosome has been the defining characteristic for a special class of TFs known as pioneer factors. Recent studies suggest TP53 functions as a pioneer factor that can target its TFBS within nucleosomes, but it remains unclear how TP53 binds to nucleosomal DNA. To comprehensively examine TP53 nucleosome binding, we comp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 73 publications
11
62
0
Order By: Relevance
“…As to the rotational setting of the Sox2 binding motif, a more accessible minor groove (facing away from the histone octamer) generally corresponds to a higher affinity. A preference for specific motif positioning in the nucleosome context has also been suggested for other TFs, such as p53, which favors exposed sites (Cui and Zhurkin, 2014) and nucleosome edges (Yu and Buck, 2019).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As to the rotational setting of the Sox2 binding motif, a more accessible minor groove (facing away from the histone octamer) generally corresponds to a higher affinity. A preference for specific motif positioning in the nucleosome context has also been suggested for other TFs, such as p53, which favors exposed sites (Cui and Zhurkin, 2014) and nucleosome edges (Yu and Buck, 2019).…”
Section: Discussionmentioning
confidence: 83%
“…Despite extensive research, the capacity of and mutual relationship between Sox2 and Oct4, and PFs in general, in targeting nucleosomal DNA remains a matter of debate (Biddle et al, 2019; Chronis et al, 2017; Franco et al, 2015; Iwafuchi-Doi et al, 2016; Soufi et al, 2015; Swinstead et al, 2016). Recent data suggested that the pioneer activity of a given TF may be conditional and dependent on the local chromatin environment (King and Klose, 2017; Liu and Kraus, 2017; Soufi et al, 2015; Swinstead et al, 2016; Yu and Buck, 2019). Popular methods of choice for studying TF-chromatin interaction, such as genome-wide binding and bulk biochemical assays, lack sufficient temporal resolution to inform the time order of binding events (usually occurring on the order of seconds) by multiple TFs.…”
Section: Introductionmentioning
confidence: 99%
“…S4F). It has been shown that P53 has pioneering activity [ 64 , 65 ] and is capable of binding nucleosomal DNA [ 66 68 ]. Hence, we performed nucleosome occupancy and phasing analysis using ATAC- [ 69 ] and MNAse-seq [ 70 , 71 ] and observed strong nucleosome phasing at P53 peaks compared to OSN-bound or randomly selected loci (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The LFY target site is near the nucleosome dyad, where it resides in vivo (Fig. 1a) and where histone-DNA interactions are strongest 58, 59 . LFY did not bind the nucleosomal substrate when its consensus motif was mutated, indicating that LFY binds the nucleosome in a sequence specific manner (Fig.…”
Section: Resultsmentioning
confidence: 99%